The philosophical values of Uba Rampe in the traditional Sebaran Apem Kukus Keong Emas ceremony - Prima Veronika; Kenfitria Diah Wijayanti; Budi Waluyo; Astiana Ajeng Rahadini; Favorita Kurwidaria; Winda Dwi Lestari; Tya Resta Fitriana; Puji Nuranisah (Universitas Islam Sultan Agung, 2026)
This study describes the philosophical value contained in the Uba Rampe of the traditional ceremony of Sebaran Apem Kukus Keong Emas. The purpose of this study is to determine the philosophical value in the Uba Rampe of the traditional ceremony of the Sebaran Apem Kukus Keong Emas. The research method used was a descriptive qualitative. The data analysis technique employed interactive analysis by Miles and Huberman, which included data collection, data reduction, data presentation, and drawing conclusions. The study applied Javanese philosophy theory by Sri Wintala Achmad. The data in this study consisted of photographs of Uba Rampe, with data sources obtained from informants and events. The sampling technique used was snowball sampling. Data were collected through observation and interviews. Data validity was tested using source triangulation and theory triangulation. The results of this study indicate the existence of philosophical value in the Uba Rampe of the traditional ceremony of Sebaran Apem Kukus Keong Emas. In addition, there is also relevance to the teaching material of narrative essays on cultural events in junior high school.